As the Heart and Not as an Appendix (2017)
In Chile, science communication projects such as Explora Chile have been being developed, which has been advancing CTI Culture. Explora Chile was born from spaces such as the national week of science where researchers talked to students, and so its purpose is to train critical people with outreach activities.